3D Heterogeneous Co3O4@Co3S4 Nanoarrays Grown on Ni Foam as a Binder‐Free Electrode for Lithium‐Ion Batteries. Issue 2 (4th December 2017) - Wang, Xia; Liu, Changkun; Li, Qiang; Li, Hongsen; Xu, Jie; Chu, Xianming; Zhang, Lijuan; Zhao, Guoxia; Li, Hongliang; Guo, Peizhi; Li, Shandong; Zhao, Xiu Song
Abstract: Co3 O4 @Co3 S4 nanoarrays on Ni foam (abbreviated as Co3 O4 @Co3 S4 NAs) were prepared by using a facile synthesis method, which involves hydrothermal preparation, low‐temperature thermal decomposition of Co(OH)y (CO3 )0.5(2‐y)  ⋅ 11H2 O, and sulfurization. The material exhibited good electrical conductivity, high specific capacity, and cycling stability with a reversible capacity of 1050 mAh g −1 at 200 mA g −1 after 40 cycles and an initial coulombic efficiency of 82.25 %. At a high current density (1500 mA g −1 ), the capacity reached up to 808.1 mAh g −1 . The excellent lithium‐storage performance of Co3 O4 @Co3 S4 NAs can be ascribed to the synergistic effect between Co3 O4 and Co3 S4, along with the contribution of the Ni foam. The method described in this paper can be extended to enhance the electrochemical performance of other metal oxides. Abstract : Non‐binding : Co3 O4 @Co3 S4 nanoflakes composed of nanorod arrays on a Ni foam are fabricated by using a facile in situ sulfurization procedure involving a simple hydrothermal treatment followed by calcination and hydrothermal processes. The anode exhibits excellent electrochemical properties for lithium‐ion batteries, ascribed to the heterostructure of Co3 O4 and Co3 S4, along with the Ni foam.